2020
DOI: 10.1111/cas.14642
|View full text |Cite
|
Sign up to set email alerts
|

RBPJ contributes to the malignancy of glioblastoma and induction of proneural‐mesenchymal transition via IL‐6‐STAT3 pathway

Abstract: Notch signaling plays a pivotal role in many cancers, including glioblastoma (GBM). Recombination signal binding protein for immunoglobulin kappa J region (RBPJ) is a key transcription factor of the Notch signaling pathway. Here, we interrogated the function of RBPJ in GBM. Firstly, RBPJ expression of GBM samples was examined. Then, we knocked down RBPJ expression in 2 GBM cell lines (U251 and T98) and 4 glioblastoma (GBM) stem‐like cell lines derived from surgical samples of GBM (KGS01, KGS07, KGS10 and KGS15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Mounting evidence indicates that inflammatory factors are found in the tumour microenvironment of many cancers 4 . Pro‐inflammatory factors have been described in glioma, and it is generally considered that IL‐6, IL‐8, CXCL1, CXCL10 and TGFβ2 are pro‐tumour cytokines closely related to glioma progression 5‐9 . Interleukin‐6 (IL‐6) is a cytokine that regulates immune and inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence indicates that inflammatory factors are found in the tumour microenvironment of many cancers 4 . Pro‐inflammatory factors have been described in glioma, and it is generally considered that IL‐6, IL‐8, CXCL1, CXCL10 and TGFβ2 are pro‐tumour cytokines closely related to glioma progression 5‐9 . Interleukin‐6 (IL‐6) is a cytokine that regulates immune and inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%
“…4 Pro-inflammatory factors have been described in glioma, and it is generally considered that IL-6, IL-8, CXCL1, CXCL10 and TGFβ2 are protumour cytokines closely related to glioma progression. [5][6][7][8][9] Interleukin-6 (IL-6) is a cytokine that regulates immune and inflammatory reactions. It is expressed in various solid tumours and promotes the invasion and migration of tumour cells.…”
mentioning
confidence: 99%
“…In order to verify the function of NPC2 in GBM, we silenced NPC2 in GBM cells. U87-MG and U251 are cell lines often used in the study of GBM ( Gao et al, 2020 ; Tu et al, 2020 ; Xia et al, 2020 ; Zhang G. et al, 2020 ). CCK-8 assay has shown that cell proliferation was inhibited in U87-MG and U251 cells with Sh-NPC2 transfection compared with that in negative control (Sh-NC) ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…TST is mainly localized to mitochondria and catalyzes the conversion of thiosulfate and cyanide to thiocyanate and sulfite [ 55 ]. As molecular switches in regulating the notch response, transcription factor RBPJ involves in the regulation of the progression of a variety of tumors, such as colorectal cancer [ 56 ], lung cancer [ 57 ], hepatocellular carcinoma [ 58 ], glioblastoma [ 59 , 60 ], and prostate cancer [ 61 ]. As a member of the G protein family, GNA11 plays an important role in tumor progression [ 62 ].…”
Section: Discussionmentioning
confidence: 99%